Carbon Taxes and Tariffs, Financial Frictions, and International Spillovers - Stefano Carattini; Giseong Kim; Givi Melkadze; Aude Pommeret (Center for Economic Studies and ifo Institute (CESifo), 2023)
Ambitious climate policy, coupled with financial frictions, has the potential to create macrofinancial stability risk. Such stability risk may expand beyond the economy implementing climate policy, potentially catching other countries off guard. International spillovers may occur because of trade and financial channels. Hence, we study the design and effects of climate policies in the world economy with international trade and financial flows. We develop a two-sector, two-country, dynamic general equilibrium model with financial frictions, climate policies, including carbon tariffs, and macroprudential policies. Using the calibrated model, we evaluate spillovers from unilateral domestic carbon pricing to foreign economies and back. We also examine more ambitious climate architectures involving carbon tariffs or a global carbon price. We find that accounting for cross-border financial flows and frictions in credit markets is crucial to understand the effects of climate policies and to guide the implementation of macroprudential policies at the global scale aimed at minimizing transition risk and paving the way for ambitious climate policy.
Keywords: E44; E58; F38; F42; G18; Q58; 330; financial frictions; carbon tax; carbon tariffs; open economy